Unusual Two‐Step Assembly of a Minimalistic Dipeptide‐Based Functional Hypergelator. Issue 9 (27th January 2020) - Chakraborty, Priyadarshi; Tang, Yiming; Yamamoto, Tomoya; Yao, Yifei; Guterman, Tom; Zilberzwige‐Tal, Shai; Adadi, Nofar; Ji, Wei; Dvir, Tal; Ramamoorthy, Ayyalusamy; Wei, Guanghong; Gazit, Ehud
Abstract: Self‐assembled peptide hydrogels represent the realization of peptide nanotechnology into biomedical products. There is a continuous quest to identify the simplest building blocks and optimize their critical gelation concentration (CGC). Herein, a minimalistic, de novo dipeptide, Fmoc‐Lys(Fmoc)‐Asp, as an hydrogelator with the lowest CGC ever reported, almost fourfold lower as compared to that of a large hexadecapeptide previously described, is reported. The dipeptide self‐assembles through an unusual and unprecedented two‐step process as elucidated by solid‐state NMR and molecular dynamics simulation. The hydrogel is cytocompatible and supports 2D/3D cell growth. Conductive composite gels composed of Fmoc‐Lys(Fmoc)‐Asp and a conductive polymer exhibit excellent DNA binding. Fmoc‐Lys(Fmoc)‐Asp exhibits the lowest CGC and highest mechanical properties when compared to a library of dipeptide analogues, thus validating the uniqueness of the molecular design which confers useful properties for various potential applications. Abstract : A de novo designed dipeptide exhibits an unusual two‐step growth process and self‐assembles into a hydrogel at a very low concentration (0.002 wt%), the lowest gelation concentration reported so far. The hydrogel can act as a 3D scaffold for cells. Composite hydrogels of the dipeptide and polyaniline exhibit ohmic conductivity and can bind to DNA.